The Relationship Between Breast Feeding and Body Mass Index and Blood Pressure in Pre-School Children - Mostafa Behjati-Ardakani; Motahareh Golestan; Zia Islami (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: It is generally accepted that breast feeding has a beneficial effect on the health of infants and children. The evidence that breast feeding protects against obesity is inconclusive also the influence of breast feeding on blood pressure in later life is uncertain. The major aim of this study was to assess the association between method of infant breast feeding and components of the body mass index and blood pressure in pre-school children. Materials & Methods: In a cohort study, a total of 800 pre-school children, 359 (47.2%) males, and 402 (52.8%) females, born in 2003 in Yazd, Iran were selected based on a systematic stratified random model. Of eight hundred questionnaires sent, 761 (95%) were returned to the investigators. At 6 years, blood pressure was measured on the right arm at rest. Body mass index (BMI) was calculated by dividing the weight in kilograms by the square of height in meters (kg/m2).Data on infants feeding were collected respectively during first two years of life .Data were managed and analyzed using SPSS (SPSS, Inc, version 13.0) Results: Of the 761 subjects included in this study, 452 (59.4%) were exclusively breast fed, 136 (17.9%) were bottle fed and 173 (22.7%) were partially breast fed. Body mass index was not significantly different between bottle feeding, partial and exclusive breast feeding groups (P=0.398) ..No relationship was found between method and duration of breast feeding, and systolic blood pressure (P=0.244), diastolic blood pressure (P=0.781) and mean blood pressure (P=0.483). Conclusion: We did not find association between method of infant feeding, duration of breast feeding and systolic, diastolic mean blood pressures and also with body mass index